Polimorfismo gênico de receptores TLRs e citocinas: papel na resposta imune em pacientes com tuberculose pulmonar - Peresi, Eliana [UNESP] (2012)
It is estimated that one-third of the total world population is latently infected with M. tuberculosis and only 5-10% of the infected individuals will develop active TB disease during their life-time. The reason why some infected individuals develop active disease, while others do not is not yet entirely understood. Given the central role of TLR-2 in the incitement of inflammation, polymorphisms in its gene might be involved in both infectious and inflammatory diseases. The aim of this study was to evaluate the influence of TLR2 - 16934A/T and GT repeat polymorphisms on the immune response of PTB patients undergoing anti-TB treatment at different time points of anti-tuberculosis treatment: T1 (beginning), T2 (3 months) and T3 (end). For this we genotyped TLR2 -16934 and (GT)n repeats polymorphisms and evaluated the immune response of pulmonary tuberculosis patients during the time of anti-tuberculosis treatment. The present study suggests that TLR2 - 16934A/T and GT repeats polymorphisms can influence differential TLR-2, NF-κB and cytokine levels during anti-TB treatment. We also suggest that PTB patients with TLR2 - 16934 AA genotype may have a worst outcome of the disease, since they have a lower IFN-γ, cytokine essential to initiate the protective immunity to active TB. This association could not be made in our study due to the low number of patients evaluated. Since TLR-2 play a major role in initiating immune response against M. tuberculosis other polymorphisms in TLR2 would be crucial to better understand protective immune responses and may serve as biomarkers of protection or susceptibility to TB